Критерии оптимизации турбокомпаундных транспортных двигателей - Алёхин, Сергей Алексеевич; Герасименко, Владимир Петрович (НТУ "ХПИ", 2014)
Описаны особенности выбора типов двигателей для различных транспортных средств, условий эксплуатации, а также оценки их эффективности. Выполнен анализ критериев эффективности транспортных средств при оптимизации их двигателей. Установлена применимость некоторых аналогов для оценки эффективности наземных транспортных машин. Показаны связи удельных параметров двигателей с некоторыми критериями эффективности.

The peculiarities of the choice of the engine type for different transport facilities, operation conditions and also the estimation of their efficiency have been described. The efficiency criteria of the transportation facilities during the optimization of their engines have been analyzed. The applicability of some analogous facilities to evaluate the efficiency of surface transport vehicles has been established. The relations of the specific parameters of the engines to some efficiency criteria have been shown.
Optimization criteria of turbocompound transport engines
Keywords: газотурбинный двигатель; поршневой двигатель; наземная транспортная машина; мощность; критерий эффективности; gas turbine engine; piston engine; surface transport machine; power; efficiency criterion; optimization